Comparative Study of Pyogenic Granuloma Management with Conservative Sclerotherapy to Invasive Surgical Excision: A Randomized Clinical Trial - Pandey, Sangita; Usman, Neha; Saleh, Muhammad Imran; Akhtar , Muhammad Usman (Nepal Journal of Health Sciences, 2024)
Introduction: Pyogenic granuloma is a common benign reactive mucocutaneous lesion. Various treatment options like excision, sclerotherapy, cryotherapy, laser is widely practiced. Objective: This study was conducted to determine and compare the effect of 3% sodium tetradecyl sulfate to surgical excision in the management of oral pyogenic granuloma. Methods: The prospective randomized controlled trial was conducted among two equal randomly allocated groups (48 each) of histologically confirmed cases. Group A was treated by surgical excision while group B was treated by 3% STDS. Both groups were evaluated weekly for a month for pain and healing and 1st, 3rd & 6th for recurrence. Results: Pain score is statistically significant on 1st and 2nd week follow up. No clinical and statistical difference observed in pain on 3rd and 4th week. Clinically significant recurrence was observed in group ‘A’ (4.1%) than group ‘B’ on 3 months but was statistically insignificant. 1 recurrence was observed in group ‘B’ on 6 months whereas, 3 were reported from group ‘A’ in the same duration. Healing on 1st and 2nd weeks were comparable and statistically significant in both groups however the results failed to show any significant difference on 3rd and 4th week. The demographics showed mean age 30.97±12.4 years with 60.42% of incidence in female and the commonest site being mandibular anterior teeth (25%). Conclusion: Although, surgical excision is commonly practiced, it is associated with higher recurrence, increased pain score & prolonged healing period. On contrary, sclerotherapy with 3% STDS proved to be safer, minimally invasive and more accepted by patients with minimum postoperative morbidity.